PID Parameters Auto-Tuning on GPS-based Antenna Tracker Control using Fuzzy Logic - Ahmad Riyandi; Sumardi Sumardi; Teguh Prakoso (Jurnal Teknologi dan Sistem Komputer, 2018)
The moving vehicles require an antenna to communicate which is placed on the vehicles and at the ground station (ground control station, GCS). Generally, GCS uses a directional antenna equipped with the drive system with the conventional proportional, proportional-integral, or proportional-integral-derivative (PID) control, and step-tracking algorithms based on the received signal strength indicator (RSSI). This research used PID control method tuned with fuzzy logic based on Global Positioning System (GPS) to control a directional antenna at GCS. The resulting antenna tracker system was capable of tracking objects with a minimal error of 0° at azimuth and elevation angle and had a maximal error of 49° for a 49 km/hour speed object. The system had an average rise time of 0.7 seconds at an azimuth angle and 1.08 seconds at an elevation angle. This system can be used to control antenna direction for moving vehicles, such as an unmanned aerial vehicle (UAV) and rocket.